The Science of Recovery: Optimising Post-Exercise Muscle Healing - Shubham Bharad (PT) (Medical Science: Trends and Innovations Vol. 13, 2025)
This chapter provides an in-depth examination of muscle recovery following exercise, focusing on the complex physiological processes that underlie muscle healing and adaptation. It details the inflammatory response, muscle protein synthesis, and the role of satellite cells, as well as the critical functions of oxygen and nutrient delivery. The chapter integrates traditional recovery practices-such as sleep, nutrition, and physical therapies-with advanced interventions including cryotherapy, pneumatic compression, blood flow restriction (BFR) therapy, low-level laser therapy, hyperbaric oxygen therapy, and electrical muscle stimulation. Emerging technologies, such as wearable sensors and AI-driven recovery platforms, are highlighted for their role in providing personalised recovery strategies. Future trends in genomic and proteomic profiling, along with regenerative medicine approaches like stem cell therapy, are also discussed.